Bontoc pattong dance, music and costumes as culturally-relevant teaching materials for special learners - Holgado, Victoria Tacay Palaleo (2009)
The Bontoc pattong dance, music, and costumes were chosen by the researcher to be used as culturally relevant teaching materials to nine children with mental retardation and who are hard of hearing in a Bontoc special school. The use of familiar, culturally relevant materials enhanced the special learners' self-confidence and improved their sense of physical well-being and instilled understanding and appreciation of their culture. Teachers observation and interviews with the parents and participating children showed that pattong dance, music and costumes are beneficial to the children's self-confidence. It was concluded that pattong dance, music and costumes and other culturally relevant materials can be used in teaching special learners particularly the children with mental retardation and who are hard of hearing in Bontoc, Mountain Province.